2019
DOI: 10.1186/s13039-019-0414-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular findings in nine new cases of tetrasomy 18p syndrome: FISH and array CGH characterization

Abstract: BackgroundSmall Supernumerary Marker Chromosomes (sSMC) are rare chromosomal abnormalities, which have abnormal banding arrangement and take many shapes. Several disorders have been correlated with sSMC presence. The aim of this study is to characterize the sSMC derived from chromosome 18 by Fluorescence in situ hybridization (FISH) and Array Comparative Genomic Hybridization (aCGH).ResultsNine children with dysmorphic features have been investigated. They have these features in common: a triangular face, low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The consistent findings were global developmental delay/mental retardation, abnormal muscle tone, brain MRI abnormalities, feeding difficulties, and microcephaly. A similar but milder phenotype is present in the rare cases of high-level mosaicism (Bai et al, 2017;Slimani et al, 2019), which is consistent with a clinical picture of the proband. with our PDMZTs is given in Table S2.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The consistent findings were global developmental delay/mental retardation, abnormal muscle tone, brain MRI abnormalities, feeding difficulties, and microcephaly. A similar but milder phenotype is present in the rare cases of high-level mosaicism (Bai et al, 2017;Slimani et al, 2019), which is consistent with a clinical picture of the proband. with our PDMZTs is given in Table S2.…”
Section: Discussionsupporting
confidence: 79%
“…We describe a pair of PDMZTs where phenotypic features of the proband are due to mosaic tetrasomy 18p, which is preferentially present in the tissues of ectodermal origin. Tetrasomy 18p [or isochromosome 18p, i(18p)] is a rare syndrome (OMIM #614290) involving feeding difficulties, neonatal respiratory distress, growth retardation, microcephaly, developmental delay, muscle tone abnormalities, various congenital anomalies, and characteristic dysmorphism (Sebold et al, 2010; Slimani et al, 2019). Most cases are de novo aberrations, although there are familial examples (Abeliovich et al, 1993; Boyle et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…No abnormality was found in the ultrasound of Case 24. Isochromosome 18p syndrome would cause growth and mental retardation, neonatal respiratory distress, and characteristic dysmorphism [ 15 , 16 ]. Case 25 was found to have r(Y).…”
Section: Discussionmentioning
confidence: 99%
“…The CMA result of Case 24 demonstrated that the CNV was pathogenic. The duplication contains 54 OMIM genes, and it has been reported that tetrasomy18p would cause developmental delay and intellectual disability [ 15 , 16 ]. Six cased continued the pregnancy and the babies were phenotypically normal at birth.…”
Section: Discussionmentioning
confidence: 99%
“…CGH 4x44K micro-array was performed using the agilent platform as previously described ( 11 , 12 ). Agilent ® oligonucleotide array was performed according to the manufacturer’s instructions (Agilent Human Genome CGH Microarray kit 44K ® ).…”
Section: Methodsmentioning
confidence: 99%